A well-defined, versatile photoinitiator (salen)Co–CO2CH3 for visible light-initiated living/controlled radical polymerization1. Issue 5 (20th May 2015) - Zhao, Yaguang; Yu, Mengmeng; Zhang, Shuailin; Wu, Zhenqiang; Liu, Yuchu; Peng, Chi-How; Fu, Xuefeng
<x xml:space="preserve">Abstract</x> A well-defined organocobalt salen complex (salen)Co–CO2CH3 is used as a versatile photoinitiator for visible light-initiated living radical polymerization.